The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States

Digenic inheritance of an SMCHD1 mutation and an FSHD-permissive D4Z4 allele causes facioscapulohumeral muscular dystrophy type 2. - Lemmers, Richard J L F; Tawil, Rabi; Petek, Lisa M; Balog, Judit; Block, Gregory J; Santen, Gijs W E; Amell, Amanda M; van der Vliet, Patrick J; Almomani, Rowida; Straasheijm, Kirsten R; Krom, Yvonne D; Klooster, Rinse; et al. (Nat Genet, 2012)
Facioscapulohumeral dystrophy (FSHD) is characterized by chromatin relaxation of the D4Z4 macrosatellite array on chromosome 4 and expression of the D4Z4-encoded DUX4 gene in skeletal muscle. The more common form, autosomal dominant FSHD1, is caused by contraction of the D4Z4 array, whereas the genetic determinants and inheritance of D4Z4 array contraction-independent FSHD2 are unclear. Here, we show that mutations in SMCHD1 (encoding structural maintenance of chromosomes flexible hinge domain containing 1) on chromosome 18 reduce SMCHD1 protein levels and segregate with genome-wide D4Z4 CpG hypomethylation in human kindreds. FSHD2 occurs in individuals who inherited both the SMCHD1 mutation and a normal-sized D4Z4 array on a chromosome 4 haplotype permissive for DUX4 expression. Reducing SMCHD1 levels in skeletal muscle results in D4Z4 contraction-independent DUX4 expression. Our study identifies SMCHD1 as an epigenetic modifier of the D4Z4 metastable epiallele and as a causal genetic determinant of FSHD2 and possibly other human diseases subject to epigenetic regulation.
Keywords: Adult; Aged; Chromosomal Proteins, Non-Histone; Chromosomes, Human, Pair 18; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Haplotypes; Heredity; Homeodomain Proteins; Humans; Male; Middle Aged; Muscular Dystrophy, Facioscapulohumeral; Mutation

Facioscapulohumeral muscular dystrophy: consequences of chromatin relaxation. - van der Maarel, Silvère M; Miller, Daniel G; Tawil, Rabi; Filippova, Galina N; Tapscott, Stephen J (Curr Opin Neurol, 2012)
PURPOSE OF REVIEW: In recent years, we have seen remarkable progress in our understanding of the disease mechanism underlying facioscapulohumeral muscular dystrophy (FSHD). The purpose of this review is to provide a comprehensive overview of our current understanding of the disease mechanism and to discuss the observations supporting the possibility of a developmental defect in this disorder. RECENT FINDINGS: In the majority of cases, FSHD is caused by contraction of the D4Z4 repeat array (FSHD1). This results in local chromatin relaxation and stable expression of the DUX4 retrogene in skeletal muscle, but only when a polymorphic DUX4 polyadenylation signal is present. In some cases (FSHD2), D4Z4 chromatin relaxation and stable DUX4 expression occur in the absence of D4Z4 array contraction. DUX4 is a germline transcription factor and its expression in skeletal muscle leads to activation of early stem cell and germline programs and transcriptional activation of retroelements. SUMMARY: Recent studies have provided a plausible disease mechanism for FSHD in which FSHD results from inappropriate expression of the germline transcription factor DUX4. The genes regulated by DUX4 suggest several mechanisms of muscle damage, and provide potential biomarkers and therapeutic targets that should be investigated in future studies.
Keywords: Animals; Chromatin; Homeodomain Proteins; Humans; Muscle, Skeletal; Muscular Dystrophy, Facioscapulohumeral; Transcription, Genetic